Deep obturator lymph node dissection in gynaecological cancer patients: Is it feasible and useful?. (17th August 2016) - Padak, Ahmet; Kasap, Burcu; Yetimalar, Hakan; Kılıç Sakarya, Derya; Yiğit, Seyran
Abstract : Our aim was to investigate the feasibility and outcomes of deep obturator lymph node (DOLN) dissection in gynaecological cancer patients. A prospective study included 62 patients with a diagnosis of ovarian, endometrial or cervical cancer who underwent surgery. In the study group, 36 patients underwent obturator lymph node dissection above and under the obturator nerve, while 26 control group patients underwent routine obturator lymph node dissection above the obturator nerve. Groups were compared with respect to dissected lymph node count, intraoperative characteristics and early postoperative complications. Total lymph node count in the DOLN dissected group was greater than that in the control group, and the difference was statistically significant. No statistically significant difference was found between the groups, regarding postoperative complications and intraoperative characteristics. The total number of lymph nodes dissected by using DOLN dissection increased without an increase in intra- and postoperative complications in gynaecological cancer patients.